Pengaruh User Generated Content Dan Electronic Word Of Mouth Terhadap Brand Trust Produk Kosmetik Hanasui Pada Aplikasi Tiktok - Agustina, Dinda Eka; Mahendri , Wisnu (Jurnal Bisnis Mahasiswa, 2023)
This research was conducted to find out how user-generated content (UGC) and electronic word of mouth (e-WOM) influence the brand trust of Hanasui cosmetic products in the Tiktok application. This type of research is quantitative research. The population of this study is users of the Tiktok application in Jombang Regency, East Java, with a minimum age range of 11-31 years. The sampling method in this study used a purposive sampling technique which obtained a total sample of 96 people. The data collection technique was distributing questionnaires online through Google Forms, then processing them using SPSS for Windows version 26. The conclusions from this study indicate that user-generated content has a positive and significant effect on brand trust, and electronic word of mouth has a positive and significant effect on brand trust